PENERAPAN METODE TREND MOMENT DALAM PRDIKSI PENJUALAN OBAT HERBAL KOLESTROL - Ilham Pramudya; Abednego Maruli Hotasi Sinaga; Sri Rezekiana iregar; Siti Aisyah (Politeknik Bisnis Indonesia, 2023)
This research aims to solve problems in inventory management of cholesterol-lowering herbal medicines at PT. Canaya Sirna Sentosa. Currently, the company is facing difficulties in procuring production materials due to irregular sales of herbal cholesterol medicines, causing inappropriate stock and resulting in losses. This research proposes a prediction system using the trend moment method to help companies manage inventory. This application allows input of product and sales data, as well as providing predicted results for the amount of herbal medicine inventory for a certain period. From the results of data processing obtained from 2018 to January 2023, the total data for sales forecasting/prediction is 42 bottles. The research results show that the trend moment method is effectively used as a prediction tool to reduce the error rate in determining the amount of herbal medicine inventory. This application system provides convenience and speed in data collection and can be a solution to overcome the problem of forecasting the amount of herbal medicine supplies in the future. The use of the trend moment method in this research can increase efficiency and accuracy in herbal medicine inventory management at PT. Canaya Sirna Sentosa, and can minimize losses due to inappropriate stock.